From hemangioblast to hematopoietic stem cell: an endothelial connection? - Jaffredo, T; Nottingham, W; Liddiard, K; Bollerot, K; Pouget, C; De Bruijn, M (2005)
The developmental origin of hematopoietic stem cells has been the subject of much research. Now that the developmental link between the hematopoietic system and the vasculature has been well established, questions remain regarding the precise cellular origin of definitive hematopoietic cells and at what point they branch off from the endothelial lineage. Do they emerge directly from a hemangioblast-type cell, similar to what is proposed for primitive yolk sac hematopoiesis, or are they generated via an endothelial intermediate, the hemogenic endothelium? In this review, we will give an overview of the data obtained from the mouse and avian models on the cellular origins of the hematopoietic system.